Allelopathic Effect of Alternanthera paronychioides L. Roots and Leaves Extracts on Seedling Growth of Raphanus sativa L. - Qadeer, Abdul; Ijaz, Yumna; Shah, Mohib; Khan, Wasim; Begum, Syeda Sundas; Ahmad, Awais; Bibi, Sania; Gul, Fathma; Gul, Safia; Ali, Syed Maqsood; Ali, Mansoor; Rasheed, Shayan (Indus Journal of Bioscience Research, 2025)
Allelopathy is a biological process whereby plants secrete certain chemicals through their roots, shoots or leaves, called allelochemicals. These chemicals directly cause some biological responses among nearby plants, microorganisms, or even small animals. The allelochemicals represent a large group of compounds, including leachate, root exudates, volatiles or even debris decomposed from the parts of the plant, which have appreciable allelopathic effects ranging from germination, seedling, and overall productivity drawbacks to nearby species. The present study includes the evaluation of allelopathy of the plant Alternanthera paronychioides using its aqueous extracts on the seed germination and early growth of Raphanus sativus (radish) seedlings. The dried plant parts (particularly the A. paronychioides leaves and roots) have undergone aqueous extraction and tested on the R. sativus seeds under controlled experimental conditions. Seedling development was found to be severely suppressed in terms of germination; both root and leaf extracts showed highly significant declines in their germination percentages, radicle, and plumule (shoot) growth. The effect was more pronounced with the increasing concentration on the inhibition effects; it showed that R. sativus seedlings were inhibited in the root and shoot lengths as the concentration of A. paronychioides extracts was increased, showing very aggressive phytotoxic effect. This means that with greater concentrations of allelochemicals available within these extracts, greater physiological stress would be on the seedlings affecting growth processes in the normal ways. The results indicate that A. paronychioides has strong allelopathic action on R. sativus, thus supporting the view that secondary metabolites from this species can be concerning to other species in their early developmental stages. Such interactions have implications such as competitive interactions in plants and community dynamics, while in application, they must be subjected to current theory of sustainable weed management.